2011
DOI: 10.1177/0300985811412622
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Purkinje Neuron Loss and Polyglucosan Body Accumulation in Hereditary Cerebellar Degeneration in Scottish Terriers

Abstract: A hereditary cerebellar degenerative disorder has emerged in Scottish Terriers. The aims of this study were to describe and quantify polyglucosan body accumulation and quantify Purkinje neurons in the cerebellum of affected and control dogs. The brains of 6 affected Scottish Terriers ranging in age from 8 to 15 years and 8 age-matched control dogs were examined histopathologically. Counts of Purkinje neurons and polyglucosan bodies were performed in control and affected dogs on cerebellar sections stained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…These changes fit well with previous reports of CCD or cerebellar abiotrophy, where primary Purkinje neuron loss and secondary granular cell degeneration are most commonly reported [7, 11, 13, 14, 16]. Similar to previous studies, the HVs also demonstrated a characteristic distribution of cerebellar folial atrophy, with the dorsal and rostral vermis predominantly affected whilst the caudoventral regions appeared spared [10, 12, 14, 17]. Purkinje neuron loss and associated gliosis were more severe in Case 1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These changes fit well with previous reports of CCD or cerebellar abiotrophy, where primary Purkinje neuron loss and secondary granular cell degeneration are most commonly reported [7, 11, 13, 14, 16]. Similar to previous studies, the HVs also demonstrated a characteristic distribution of cerebellar folial atrophy, with the dorsal and rostral vermis predominantly affected whilst the caudoventral regions appeared spared [10, 12, 14, 17]. Purkinje neuron loss and associated gliosis were more severe in Case 1.…”
Section: Discussionsupporting
confidence: 91%
“…CCD typically causes slowly progressive clinical signs related to diffuse cerebellar dysfunction, including a dysmetric and hypermetric cerebellar ataxia, intention tremors, menace response deficits and signs of central vestibular dysfunction, including nystagmus and loss of balance [12, 16]. Age of onset of clinical signs and the rate of progression vary between breeds, ranging from neonatal, as reported in Beagles and Rhodesian Ridgebacks [3, 13], and early onset from weeks to months of age in the majority of breeds [2, 6, 8, 9, 14, 16], up to adult-onset at months to years of age with a slower progression, seen in Old English Sheepdogs, Gordon Setters and Scottish Terriers [12, 15, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, increased numbers of polyglucosan bodies are found in the molecular layer in the Scottish Terrier. 28 Morphometric study of the cerebellum in Scottish Terriers revealed that the ventral part of the cerebellum is less severely affected 28 and this feature has also been reported in several breeds, such as Finnish Hounds, Beagles, 21 Old English Sheepdogs, and Gordon…”
Section: Cerebellar Cortical Degenerationmentioning
confidence: 81%
“…Purebred dogs suffer from comparable neurodegenerative diseases affecting the cerebellar cortex referred to as cerebellar cortical degeneration, cerebellar abiotrophy or canine cerebellar or hereditary ataxia. Currently, hereditary cerebellar degenerative disorders have been described in over 20 breeds of dog [10], [11] with many more sporadic cases reported. In most dog breeds, the disorder causes slowly progressive degeneration of the cerebellar cortex, with dramatic Purkinje neuron loss resulting in a progressive gait dysfunction [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hereditary cerebellar degenerative disorders have been described in over 20 breeds of dog [10], [11] with many more sporadic cases reported. In most dog breeds, the disorder causes slowly progressive degeneration of the cerebellar cortex, with dramatic Purkinje neuron loss resulting in a progressive gait dysfunction [10], [11]. Forms that primarily target the granular layer or produce ataxia without cell loss are also reported [12]–[18].…”
Section: Introductionmentioning
confidence: 99%